STUDI ANALISIS KETIDAKPASTIAN HASIL KALIBRASI TIMBANGAN DAN MISTAR TERHADAP KEBERTERIMAAN PENGUJIAN GRAMATUR KERTAS (STUDY ON ANALYSIS OF UNCERTAINTY OF CALIBRATED VALUE FOR BALANCE AND RULER FOR THE ACCEPTANCE OF PAPER GRAMMAGE TESTING) - Darmawan Darmawan; Titik Istirohah (Center for Pulp and Paper, 2016)
Study on analysis of uncertainty of calibrated value for balance and steel ruler for the acceptance of paper grammage testing that refers to SNI ISO 536 : 2010 (grammage testing method) and SNI 14-0440-2006 (paper and carton grammage) has been done. Testing instrument must be calibrated to ensure the testing value/measurement appropriate with expected specification refers to ISO 17025 : 2008. From calibration value gained conventional truth value and uncertainty of testing instrument. Uncertainty calculation refers to “Guide to the Expression of Uncertainty in Measurement”- ISO GUM, is a reference and measurement uncertainty evaluation method that have been received internationally. This reference is also one of reference documents in ISO 17025 : 2008 (competence requirements of examination and calibration laboratory). The evaluation test showed that the deviation value is less than 4%, so that it complies with the allowed tolerance which is also 4%. The result of testing evaluation and calibration showed that balance and ruler were used in Paper Testing Laboratory of Center for Pulp and Paper was appropriate with grammage testing prerequirement. ABSTRAKStudi analisis ketidakpastian hasil kalibrasi timbangan dan mistar baja terhadap keberterimaan uji gramatur kertas yang mengacu pada SNI ISO 536 Cara uji gramatur dan SNI 14-0440-2006 Gramatur kertas dan karton telah dilakukan. Untuk menjamin hasil uji/ pengukuran sesuai dengan spesifikasi yang diinginkan menurut ISO 17025 Syarat-syarat kompetensi Laboratorium Pengujian dan Laboratorium Kalibrasi maka alat uji/ukur harus dikalibrasi. Dari hasil kalibrasi diperoleh nilai kebenaran konvensional alat ukur beserta ketidakpastiannya. Perhitungan ketidakpastian mengacu pada ISO GUM “Guide to the Expression of Uncertainty in Measurement”, yang merupakan panduan dan metode evaluasi ketidakpastian pengukuran yang diterima secara internasional. Acuan ini juga sebagai salah satu dokumen acuan dalam ISO 17025 . Dari hasil evaluasi hasil uji diperoleh penyimpangan kurang dari 4%, sehingga memenuhi toleransi yang diizinkan yaitu 4 %. Kesimpulan dari studi ini menjelaskan bahwa timbangan dan mistar baja yang digunakan oleh Laboratorium Uji Kertas Balai Besar Pulp dan Kertas memenuhi syarat uji gramatur. Kata kunci: kalibrasi, ketidakpastian, gramatur, akurasi, toleransiKata kunci: kalibrasi, ketidakpastian, gramatur, akurasi, toleransi